Manipulation of carbon framework from the microporous to nonporous via a mechanical-assisted treatment for structure-oriented energy storage. (15th April 2020) - Xu, Fei; Qiu, Yuqian; Han, Haojie; Jiang, Guangshen; Zhao, Ruoxi; Zhang, En; Li, Hejun; Wang, Hongqiang; Kaskel, Stefan
Abstract: Rationally tuning frameworks of porous carbons from the microporous to nonporous is still a challenge on a given precursor and carbonization condition. Here a simple yet general mechanical-assisted route is reported for the conversion of a microporous carbon framework into the nonporous one through applying the mechanical pressure on the precursor prior to carbonization, which generates microporous-free and low-defect carbon frameworks. While direct carbonization without pressure treatment produces microporous carbon framework under the same carbonization conditions. The results show that pressure treatment helps to retard the deprotonation and the cross-linking process while facilitating the chain scission and aromatization, thus creating more order-layered graphitic nanodomains without substantial micropores. Such a distinct framework microstructure enables the resulting carbons to exhibit advantages in task-specific energy storage applications. For example, the microporous-free carbon with low defect in microcrystallites achieves superior Na ion storage capacity, higher rate performance and unprecedented long-term cycle stability; while the carbon with microporous framework and high surface area facilitates the formation of the electrical double layer for higher capacitances in supercapacitors. Our results clearly show the facile manipulation of carbon framework from the microporous to the low-porous and their important structural aspect for task-specific electrochemical applications. Graphical abstract: Conversion from the microporous to nonporous carbon frameworks is realized via a mechanical pressure treatment of the carbon precursor. Image 1